The study of the relationship between moderate to severe sleep obstructive apnea and cognitive impairment, anxiety, and depression - Hong, Yanan; Pei, Chong; Hao, Lingli; Xu, Kang; Liu, Feifei; Ding, Zhen (Frontiers in Neurology, 2024)
Objective: The present study endeavored to investigate the interconnection between obstructive sleep apnea (OSA) and cognitive function, alongside the manifestations of depression and anxiety. Simultaneously, an analysis was conducted to discern the factors exerting influence upon cognitive function.: A cohort of 102 patients, between January 2022 and June 2023, was encompassed in the study. Employing the PSG findings, these individuals were classified into two distinct categories: the grouping consisted of those with either negligible or mild OSA, and the other comprised individuals with moderate to severe OSA. Utilizing the Montreal Cognitive Assessment (MoCA-Beijing), Stroop Color and Word Test (SCWT), Digit Span Test (DST),Self-rating Depression Scale (SDS), and Self-rating Anxiety Scale (SAS), scores were recorded and analysed for each of the respective assessments. Additionally, discrepancies and associations between these groups were also scrutinised.The group exhibiting moderate to severe OSA demonstrated significantly elevated measurements in parameters such as neck circumference, BMI, completion times for SCWT-A, B, C, Sleep Inefficiency Index (SIE), SAS, and SDS, in comparison to the no or mild OSA group. Furthermore, the moderate-severe OSA group manifested notably diminished MoCA scores in areas of visual-spatial and executive function, memory, language, abstraction, delayed recall, orientation, total MoCA score, lowest oxygen saturation (LSaO2), average oxygen saturation, DST-backward ( DST-b ) , and DST-forward ( DST-f ) , as contrasted with the no-mild OSA group. These inter-group disparities exhibited statistical significance (P<0.05). The MoCA total score portrayed inverse correlations with age, Apnea-Hypopnea Index (AHI), BMI, SIE, SAS, SDS, CT90%, AHT90%, and Hypoxic Apnea Duration (HAD) (ranging from -0.380 to -0.481, P<0.05).Conversely, it displayed positive correlations with DST-f, DST-b, LSaO2, and average oxygen saturation (ranging from 0.414 to 0.744, P<0.05). Neck circumference, AHI, and SAS were autonomously linked to MoCA scores (OR=1.401, 1.028, 1.070, P<0.05), whilst AHI exhibited an independent correlation with SDS and SAS scores (OR=1.001, P=0.003).Patients grappling with moderate to severe OSA frequently reveal cognitive impairment and concomitant emotional predicaments encompassing depression and anxiety.These manifestations share an intimate association with AHI, LSaO2, and average oxygen saturation. Notably, anxiety, when coupled with OSA, emerges as an autonomous influential element impinging upon cognitive impairment.